2009
DOI: 10.1089/dna.2008.0826
|View full text |Cite
|
Sign up to set email alerts
|

Association of C3435T Single-Nucleotide Polymorphism of MDR1 Gene with Breast Cancer in an Iranian Population

Abstract: The human multidrug resistance gene 1 (MDR1) encodes a plasma membrane, P-glycoprotein (Pgp), which functions as the transmembrane efflux pump for various structurally unrelated anticancer agents and toxins. Polymorphisms in the MDR1 gene may have an impact on the expression and function of Pgp, thereby influencing the susceptibility to various diseases, including cancer. Recently, a silent C3435T polymorphism in exon 26 of MDR1 has been reported to be associated with decreased expression of Pgp in TT genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Likewise, no significant difference was found when genotypes were analyzed in relation to the clinical-pathological features in the IDBC group (Table 3). Clinical-pathological formation can result in several cancer types (Trock et al, 1997;Tatari et al, 2009;Rao et al, 2010;Sabahi et al, 2010;Mhaidat et al, 2011). Several studies have investigated the association of the C3435T polymorphism with breast cancer development, prognosis, and treatment outcome; however, the inconsistent and contradicting evidence has led to a confused picture (Turgut et al, 2007;Huang et al, 2008;Rodrigues et al, 2008;George et al, 2009;Taheri et al, 2010;Chen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, no significant difference was found when genotypes were analyzed in relation to the clinical-pathological features in the IDBC group (Table 3). Clinical-pathological formation can result in several cancer types (Trock et al, 1997;Tatari et al, 2009;Rao et al, 2010;Sabahi et al, 2010;Mhaidat et al, 2011). Several studies have investigated the association of the C3435T polymorphism with breast cancer development, prognosis, and treatment outcome; however, the inconsistent and contradicting evidence has led to a confused picture (Turgut et al, 2007;Huang et al, 2008;Rodrigues et al, 2008;George et al, 2009;Taheri et al, 2010;Chen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…14,[18][19][20][24][25][26] Several studies have considered the relationship between MDR1 expression and C3435T polymorphism examining clinical and pathological characteristics in patients with breast cancer. 11,22,23 However, the correlation was either nonsignificant or there was insufficient data. A significant association between patients with DIC and lobular invasive carcinoma was observed (T vs C: P ¼ 0.024) in the group we tested.…”
Section: Discussionmentioning
confidence: 98%
“…Our results were gained in contrast to work carried out by other researchers, who observed no significant differences in genotype and allele frequencies between Iranian patients with breast cancer and control subjects (P ¼ 0.744 and 0.590, respectively). 23 Furthermore, the C3435T genotype-related disease risk has been studied in several other cancers (renal cell carcinoma, colon cancer, lung cancer, acute lymphoblastic and myeloid leukemia, glioma) with mixed and inconsistent results. 14,[18][19][20][24][25][26] Several studies have considered the relationship between MDR1 expression and C3435T polymorphism examining clinical and pathological characteristics in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1 There are several reports which showed no significant differences between C3435T MDR1 gene polymorphisms and other diseases, In the study done by Tatari et al, it was shown there were no significant differences in genotypes and allele frequencies between patients with breast cancer and control subjects in an Iranian population. 13 Kim et al suggested C3435T polymorphism in the multidrug-resistant epilepsy may not be significant in Korean populations. 14 However, the association of C3435TMDR1 gene polymorphism with incidence of different diseases is yet controversial.…”
Section: Discussionmentioning
confidence: 99%